0571 Repolarization Variability Predicts Cardiovascular Death in Obstructive Sleep Apnea. (27th May 2020) - Patel, S I; Zareba, W; Couderc, J; Xia, X; LaFleur, B; Torabzadeh, E; Woosley, R; Parthasarathy, S
Abstract: Introduction: Patients with untreated obstructive sleep apnea (OSA) have a 2-3—fold increased risk of cardiovascular mortality (CVD) compared with individuals without OSA. QTc prolongation and increased QT variability among OSA patients may contribute to this association. Methods: Patients with OSA from the Sleep Heart Health study were identified based on polysomnography criteria and their continuous electrocardiograms (ECG) analyzed for QTc duration and QT variability. Both Fridericia's and Bazett's heart rate corrections were used to calculate QTc. QT variability was measured as standard deviation of QT intervals (SDQT) and normalized QT interval variance (QTVN) at 1- and 5-minute intervals and short-term interval beat-to-beat QT variability (STVQT) was measured at 5-minute intervals. Lasso with elastic-net regularization was used as the variable/covariate selection method. Cox proportional hazards regression models were used to determine predictors of CVD. Results: Data from 365 patients with OSA were screened. Ninety-seven patients were excluded from analysis due to low quality ECG data (n=50) or extremely high (> ln (10)) variability in QT/QTc and/or QT variability (n=12). Fifty two percent of the sample was male with mean age 65 years (±10). Fifty-six of these patients died of CVD. The mean (SD) QTc in the group that died was 411 (30) ms and 416 (34) ms compared to 406 (24) ms and 411 (25) ms using Fridericia (Cox LR p-value 0.055) and Bazett (p=0.090), respectively. Gender, age, race, diabetes, SDQT and STVQT were significant predictors for CVD. We fit models with the covariates and SDQT (at both 1 and 5 min) and STVQT as three models and demonstrate that both SDQT and STVQT are significantly associated with CVD death (p-values of 0.0048, 0.0089, and 0.0113, respectively) and all models had high area under the curve (0.8095, 0.8085, and 0.8125, respectively). Conclusion: In patients with OSA, QT variability was associated with CVD. Support: American Academy of Sleep Medicine Foundation